Examining Gender Representation in an Indonesian EFL Textbook - Agni, Zango Anisa; Setyaningsih, Endang; Sarosa, Teguh (Register Journal, 2020)
Considering its influential role in students’ behavior and attitudes, a textbook has to reflect balanced images and information about males and females. It also has to support broad choices and many roles for both sexes to avoid unjust or bias gender issues. This study aimed at examining whether an EFL textbook published by the Indonesian government promotes gender equity by (1) mapping the proportion of textual and visual representation of males and females in the textbook; (2) describing how males and females are treated in the textbook. Through content analysis, the study revealed that the book is gender-biased as indicated from unbalanced (1) textual and visual representation (2) variety of activity, role, and occupation, (3) order of mention, and (4) adjectival portrayal. In all indicators, the female is underrepresented, hidden, and framed within traditional gender stereotyping.  Reflecting on these findings, revision by the government and/ or careful treatment by teachers when using the book are ushered.  Keywords: bias, content analysis, gender representation, gender stereotype, textbook.